Galectin-3 did not associate with malaria-related insulin resistance in diabetic and non-diabetic respondents at a Ghanaian General Hospital - Emmanuel Nortey; Leonard Derkyi-Kwarteng; Daniel Amoako-Sakyi; Ansumana Sandy Bockarie; Samuel Yeboah; Samuel Acquah (PLoS ONE, 2025)
Background Malaria remains endemic in the sub-Saharan African region. The region also faces the world’s highest increase in incidence of type 2 diabetes mellitus (T2DM). Although galectin-3 has been explored in numerous conditions, scientific information on the relationship between malaria-related insulin resistance and circulating galectin-3 levels is limited. Therefore, the current study examined the association between galectin-3 and insulin resistance in diabetic and non-diabetic adults with or without malaria at the Tema General Hospital. Methods Anthropometric indices, blood pressure, glucose, full blood count (FBC), lipid profile, insulin and galectin-3 levels were measured under fasting conditions. Insulin resistance and beta-cell function were assessed using the homeostatic model assessment of insulin resistance (HOMA-IR) and beta-cell function (HOMA-B) formulae. Results Participants with T2DM were older (P < 0.05) with higher levels of systolic blood pressure and glucose but lower parasite levels than their non-diabetic counterparts. Irrespective of diabetes status, levels of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and galectin-3 were higher but triglyceride level was lower in participants with malaria. Levels of insulin, HOMA-B and HOMA-IR were highest for diabetics without malaria with high strengths of the associations. Galectin-3 could neither predict HOMA-B nor HOMA-IR in any of the study groups. Irrespective of malaria or diabetes status, insulin resistance associated with glucose (B = 0.603, Wald = 10.52, Exp (B) = 1.83, CI: 1.27–2.63; P = 0.001) and insulin (B = 1.145, Wald = 18.61, Exp (B) = 3.14, CI: 1.87–5.23; P < 0.001) levels in our context with the model explaining 67.7% (Cox & Snell R2 = 0.677) to 91% (Nagelkerke R2 = 0.91) of the observed variation. Conclusion The relationship of galectin-3 with HOMA-IR and HOMA-B appears more complex than a linear fashion in our setting.